Conductive microsphere with surface protrusion structure and preparation method and application thereof
By forming a polymer cladding layer on the surface of the core microspheres of the conductive microspheres and depositing a metal layer, conductive microspheres with uniform and controllable surface protrusion structures are prepared, which solves the problems of high connection resistance of the conductive microspheres and prone to damage in the prior art, and achieves high-performance conductive properties and stability.
Patent Information
- Application Number
- CN202210897519.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-28
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2042-07-28
AI Technical Summary
The density and uniformity of the surface protrusion structure of existing conductive microspheres are difficult to control, resulting in high connection resistance and protrusion structures that are prone to damage, affecting the conductive properties.
Conductive microspheres with uniform, density-controllable surface protrusion structures are prepared by forming a polymer cladding layer on the surface of the core microspheres and depositing a metal layer thereon. This method ensures that the protruding structure is intact with the conductive metal layer, and avoids damage to the protruding structure.
It realizes low connection resistance and high stability of conductive microspheres, ensures uniformity and voltage resistance of conductive properties, and is suitable for high-performance microelectrode connections.
Smart Images

Figure CN115109277B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive materials, and in particular relates to a conductive microsphere with a surface protrusion structure and a preparation method and application thereof. Background Art
[0002] In electronic devices, the electrical connection between microelectrodes is achieved through anisotropic conductive materials. Common anisotropic conductive materials include anisotropic conductive tapes, anisotropic conductive pastes, anisotropic conductive sheets, etc., which usually include conductive microspheres and adhesive resins or adhesives. Among them, the performance of conductive microspheres is crucial to the quality and performance of anisotropic conductive materials. With the rapid progress and development of the miniaturization of electronic circuits in recent years, there is an urgent need to improve the conductive properties of anisotropic conductive materials. Reducing the connection resistance of conductive microspheres is one of the effective methods to improve the conductive properties of anisotropic conductive materials and is currently a hot topic of research.
[0003] Research has found that forming surface protrusions on the surface of conductive microspheres can reduce the connection resistance of conductive microspheres, and is expected to improve the conductivity of the material. CN103222013A discloses a conductive powder, which includes conductive particles formed by forming a metal or alloy film on the surface of a core particle, having a plurality of protrusions protruding from the surface of the film, and the protrusions include a particle connection body formed by connecting a plurality of particles of the metal or alloy in a row. The preparation method of the conductive powder is a chemical plating method. When chemical plating is performed on the surface of the core particle, a tiny protrusion is formed on the surface of the coating by utilizing the phenomenon of abnormal precipitation in the chemical plating reaction. However, since the protrusion formed by the abnormal precipitation method is controlled and realized by the reaction conditions of chemical plating, therefore, in order to obtain a protrusion with good adhesion that breaks through the adhesive resin degree of the anisotropic conductive film, the density, uniformity and size of the protrusion are greatly restricted, and the preparation difficulty is high, and it is difficult to fully ensure conductivity.
[0004] CN103748637A discloses a conductive particle, which includes a base material particle, a conductive layer disposed on the surface of the base material particle and having a plurality of protrusions on the outer surface, and a plurality of inorganic particles embedded in the conductive layer; wherein, the inner side of the protrusion on the outer surface of the conductive layer is disposed with inorganic particles, and at least a part of the plurality of inorganic particles is not in contact with the surface of the base material particle, so when the conductive particles are used for connecting between electrodes, the connection resistance can be reduced. The conductive particles are pre-plated with a layer of metal on the surface of the polymer core microsphere, and then a layer of inorganic small particles (such as silicon dioxide) is adsorbed by van der Waals force or electrostatic action, and then chemically plated to wrap these particles in the metal conductive layer; the inorganic small particles used in the particles or protrusions have a high hardness. When the conductive particles are used to prepare anisotropic conductive materials such as anisotropic conductive films, the hard inorganic small particles will damage the electrodes due to pressure during pressing, thereby causing a short circuit and affecting the normal operation of the entire electronic device.
[0005] CN101006525A discloses a conductive particle and an anisotropic conductive material using the same, wherein the surface of the base material particle of the conductive particle is coated with a conductive film, and the conductive film has raised protrusions on the surface, wherein the raised protrusions have a conductive material different from the conductive film as the core material, and an insulating coating layer or particles are provided on the periphery of the conductive particle. The conductive particle is formed by first adsorbing a layer of small metal particles (such as metal nickel particles) on the surface of the polymer core microsphere by van der Waals force or electrostatic action, and then coating these small metal particles in the metal conductive layer by chemical plating to form conductive particles with protrusions; although these small metal particles are the same component as the conductive layer, they will not damage the electrode when used as anisotropic conductive materials such as anisotropic conductive films. However, this method of adsorbing small metal particles is also greatly limited in density or uniformity, and it is difficult to fully reduce the connection resistance of the conductive microspheres. Moreover, in the prior art represented by CN101006525A and CN103748637A, in the conductive particles with protrusion structures obtained by adsorbing microspheres, the adhesion between the inner core microspheres and the protrusion core material is weak, so there is a lack of structural integrity between the surface metal layer of the protrusion, the protrusion core material and the inner core. When the conductive particles are subjected to pressure, the protrusion is easily damaged.
[0006] Therefore, developing a conductive microsphere with high density and uniformity of surface protrusions, good structural integrity, and low connection resistance without damaging the electrode is an urgent problem to be solved in the art. Summary of the invention
[0007] In view of the deficiencies in the prior art, the object of the present invention is to provide a conductive microsphere with a surface protrusion structure, and a preparation method and application thereof. Through the design of the preparation method, a polymer coating layer with a protrusion structure is formed on the surface of the inner core microsphere, and then a metal is deposited to obtain a conductive microsphere with a surface protrusion structure. The protrusion structure of the conductive microsphere is evenly dispersed, and the density and size are controllable. The overall structure of the conductive microsphere has excellent integrity and good stability, and will not cause electrode damage. It is a conductive material with outstanding comprehensive performance.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a method for preparing a conductive microsphere having a surface protrusion structure, the preparation method comprising:
[0010] The inner core microspheres and the monomers are polymerized in the presence of an initiator, a surfactant and a solvent to obtain polymer-coated microspheres with surface protrusions; the solvent comprises a mixture of water and an organic solvent;
[0011] The polymer-coated microspheres are sequentially functionalized, activated and metal layer deposited to obtain the conductive microspheres.
[0012] In the preparation method provided by the present invention, firstly, a polymer coating layer is polymerized on the surface of the inner core microsphere, and the polymer coating layer is coated on the surface of the entire inner core microsphere and has a protrusion structure with uniform distribution and controllable size, that is, a polymer-coated microsphere with a surface protrusion structure; then, the polymer-coated microsphere with a surface protrusion structure is functionalized, activated and a metal layer is deposited to obtain a conductive microsphere with a surface protrusion structure.
[0013] In the present invention, the polymerization reaction is carried out in the presence of an initiator, a surfactant and a solvent, and the solvent includes a mixture of water and an organic solvent, so as to adjust the polarity of the solvent in the reaction system, and through compounding with the surfactant, the speed and film-forming mode of the monomer polymerization on the surface of the inner core microsphere to generate the coating layer are effectively regulated, so that the formed polymer coating layer has a protrusion structure with controllable size and density and uniform distribution, and then the protrusion structure is used as a template to obtain a conductive microsphere with a surface protrusion structure.
[0014] In the present invention, the process of depositing the metal layer is a complete, continuous and uniform wrapping process. The morphology of the conductive metal layer with a surface protrusion structure is highly similar to that of the polymer coating layer with a surface protrusion structure. All the protrusion structures, the conductive metal layer and the inner core microspheres are a complete and highly tightly connected whole and will not be damaged during use (for example, when connecting electrodes and / or under pressure). Moreover, in the preparation method, the protrusion structure is generated on the surface of the inner core microsphere by the polymerization reaction of the monomer, and then the protrusion structure of the conductive metal layer is obtained using the protrusion structure of the polymer coating layer as a template. Therefore, the protrusion structure will not damage the electrode and will not cause the circuit to be broken.
[0015] Therefore, the surface of the conductive microspheres obtained by the preparation method has a protrusion structure with uniform distribution, controllable density and controllable size. When used in anisotropic conductive materials, it can break through the adhesive and communicate with the electrode, improve the contact stability between the conductive microspheres and the electrode, and reduce the contact resistance of the line connection (reduce the connection resistance). The conductive microspheres as a whole have excellent structural integrity and high stability, which effectively avoids the situation where the protrusion structure is damaged or the protrusion structure is too hard to damage the electrode, and effectively improves the stability of fine circuit conduction.
[0016] Preferably, the core microspheres include inorganic microspheres and / or polymer microspheres.
[0017] In the present invention, the material / type of the inner core microspheres can be adaptively adjusted according to the performance requirements of the conductive microspheres. For example, when the conductive microspheres are required to have a higher hardness, inner core microspheres with a higher hardness (such as inorganic microspheres) can be selected; when the conductive microspheres are required to have a certain flexibility, inner core microspheres with better flexibility (such as polymer microspheres) can be selected.
[0018] Preferably, the inner core microspheres include any one or a combination of at least two of polystyrene microspheres, polyacrylate microspheres, styrene-acrylate copolymer microspheres, silicone microspheres, silica microspheres or zirconium oxide microspheres.
[0019] In the present invention, the size of the core microspheres can be adaptively adjusted according to the size requirements of the conductive microspheres. Preferably, the particle size of the core microspheres is 0.01-100 μm, for example, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 5 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm or 90 μm, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0020] Preferably, the monomer includes any one or a combination of at least two of (meth)acrylate monomers, (meth)acrylic acid monomers, alkenyl aromatic monomers, vinyl acetate, acrylonitrile or acrylamide monomers.
[0021] Preferably, the (meth)acrylate monomer includes any one of (meth)acrylate alkyl ester, (meth)acrylate hydroxyalkyl ester or (meth)acrylate epoxyalkyl ester, or a combination of at least two thereof.
[0022] Preferably, the (meth)acrylate monomer includes any one of methyl acrylate, ethyl acrylate, butyl acrylate, tert-butyl acrylate, isooctyl acrylate, lauryl acrylate, hydroxyethyl acrylate, glycidyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, tert-butyl methacrylate, isooctyl methacrylate, lauryl methacrylate, hydroxyethyl methacrylate, glycidyl methacrylate or 1,6-hexanediol diacrylate, or a combination of at least two thereof.
[0023] Preferably, the alkenyl aromatic monomer includes any one of styrene, divinylbenzene or divinylnaphthalene, or a combination of at least two thereof.
[0024] Preferably, the monomer comprises any one or a combination of at least two of alkyl (meth)acrylate, styrene or epoxyalkyl (meth)acrylate, and exemplary combinations include but are not limited to: a combination of alkyl (meth)acrylate and epoxyalkyl (meth)acrylate, a combination of styrene and epoxyalkyl (meth)acrylate, and a combination of alkyl (meth)acrylate, styrene and epoxyalkyl (meth)acrylate.
[0025] Preferably, the mass percentage of (meth)acrylate epoxyalkyl ester in the monomer is 10-95%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%, etc., and more preferably 20-90%.
[0026] Preferably, the mass ratio of the monomer to the core microsphere is (0.01-1):1, for example, it can be 0.03:1, 0.05:1, 0.08:1, 0.1:1, 0.15:1, 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1 or 0.9:1, etc.
[0027] Preferably, the initiator comprises an oxidation-reduction initiation system, and more preferably an oxidation-reduction initiation system having high solubility in water.
[0028] Preferably, the oxidant in the oxidation-reduction initiation system comprises any one of persulfate, hydrogen peroxide or organic peroxide, or a combination of at least two thereof.
[0029] Preferably, the persulfate includes any one of potassium persulfate, sodium persulfate or ammonium persulfate, or a combination of at least two of them.
[0030] Preferably, the organic peroxide includes any one of cyclohexanone peroxide, methyl ethyl ketone peroxide, dibenzoyl peroxide, tert-butyl hydroperoxide, cumene hydroperoxide or dicumyl peroxide, or a combination of at least two thereof.
[0031] Preferably, the reducing agent in the oxidation-reduction initiation system includes any one or a combination of at least two of sodium formaldehyde sulfoxylate, sodium sulfite, sodium bisulfite, ferrous salts, cyclopentane salts (such as cobalt cyclopentane salts, manganese cyclopentane salts, vanadium cyclopentane salts or iron cyclopentane salts, etc.), sodium dithionite, tertiary amine compounds (such as N,N-dimethylaniline) or thiols.
[0032] Preferably, based on the mass of the monomer as 100%, the mass of the initiator is 0.1-3%, for example, it can be 0.15%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.3%, 1.5%, 1.7%, 1.9%, 2%, 2.2%, 2.5% or 2.8%, etc.
[0033] Preferably, the surfactant is an ionic surfactant, more preferably an anionic surfactant.
[0034] Preferably, the ionic surfactant includes any one of dodecylbenzene sulfonate, dodecyl sulfonate, dodecyl sulfate, α-olefin sulfonate or fatty acid salt, or a combination of at least two thereof, and more preferably any one of sodium dodecylbenzene sulfonate, sodium dodecyl sulfonate, sodium dodecyl sulfate or sodium oleate, or a combination of at least two thereof.
[0035] Preferably, the HLB value (hydrophile-lipophile balance) of the surfactant is ≥10, for example, it may be 10.5, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20, etc.
[0036] Preferably, based on the mass of the monomer as 100%, the mass of the surfactant is 0.1-5%, for example, it can be 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.3%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.2%, 4.5% or 4.8%, etc.
[0037] Preferably, the organic solvent is an organic solvent miscible with water.
[0038] Preferably, the organic solvent includes an alcohol solvent and / or a ketone solvent, and more preferably includes any one of ethanol, methanol or acetone, or a combination of at least two of them.
[0039] Preferably, the mass ratio of water to organic solvent in the solvent is (1-20):1, for example, it can be 1.5:1, 2:1, 2.5:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1 or 19:1, etc.
[0040] As a preferred technical solution of the present invention, the organic solvent in the solvent acts as a polarity regulator, is mixed with water in a specific ratio, and is compounded with an ionic surfactant, which can effectively regulate the polymerization rate and polymerization behavior of the monomer and the film-forming method on the surface of the core microsphere, so that the formed polymer coating layer has a protrusion structure with uniform distribution, high density, and controllable size. If no organic solvent is contained or the amount of organic solvent is too small, it is difficult to form a suitable protrusion structure; if the amount of organic solvent is too high, the monomer will be polymerized to form polymer spheres, which cannot be effectively coated on the surface of the core microsphere.
[0041] Preferably, the polymerization reaction temperature is 50-90°C, for example, it can be 52°C, 55°C, 58°C, 60°C, 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C, 80°C, 82°C, 85°C or 88°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0042] Preferably, the polymerization reaction time is 0.5-6h, for example, it can be 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h or 5.5h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0043] Preferably, the functionalization method is to make the polymer-coated microspheres contain functional groups, and the functional groups include any one or a combination of at least two of hydroxyl, carboxyl, amino, thiol or triphenylphosphine; the functional groups have good adsorption effects on metal (precious metal) ions.
[0044] Preferably, the functionalized reagent comprises any one of a hydroxyl-containing compound, a carboxyl-containing compound or an amino-containing compound, or a combination of at least two thereof, and more preferably an amino-containing compound.
[0045] Preferably, the functionalized reagent includes any one of ethylenediamine, hexamethylenediamine or dihydroxymethylamine, or a combination of at least two thereof.
[0046] Preferably, the mass ratio of the functionalized reagent to the polymer-coated microspheres is (0.1-2):1, for example, it can be 0.2:1, 0.3:1, 0.5:1, 0.7:1, 0.9:1, 1:1, 1.2:1, 1.5:1 or 1.8:1, etc.
[0047] Preferably, the functionalization temperature is 50-100°C, for example, it can be 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C or 95°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0048] Preferably, the functionalization time is 5-24h, for example, it can be 6h, 8h, 10h, 12h, 14h, 15h, 16h, 18h, 20h, 22h or 23h, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0049] Preferably, the functionalization step is performed in the presence of a solvent.
[0050] Preferably, the solvent includes any one of water, alcohol solvents or ketone solvents, or a combination of at least two of them, and more preferably any one of water, methanol, ethanol or acetone, or a combination of at least two of them.
[0051] Preferably, a sensitization step is further included between the functionalization and the activation.
[0052] Preferably, the sensitizing solution is a stannous chloride solution; and the sensitizing step allows tin ions to be adsorbed onto the surface of the microspheres.
[0053] Preferably, the concentration of stannous chloride in the stannous chloride solution is 3-30 g / L, for example, 4 g / L, 5 g / L, 6 g / L, 8 g / L, 10 g / L, 12 g / L, 15 g / L, 18 g / L, 20 g / L, 22 g / L, 25 g / L or 28 g / L, etc.
[0054] Preferably, the sensitization temperature is 30-50°C, for example, it can be 31°C, 33°C, 35°C, 37°C, 39°C, 40°C, 41°C, 43°C, 45°C, 47°C or 49°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0055] Preferably, the sensitization time is 1-30 min, for example, it can be 2 min, 5 min, 8 min, 10 min, 12 min, 15 min, 18 min, 20 min, 22 min, 25 min or 28 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0056] Preferably, the activated activation solution comprises a mixture of a palladium salt (such as palladium chloride) and a reducing agent.
[0057] Preferably, the reducing agent comprises any one of hypophosphite, phosphite or borohydride, or a combination of at least two thereof.
[0058] Preferably, the reducing agent includes any one of sodium hypophosphite, potassium hypophosphite, sodium phosphite, potassium phosphite, sodium borohydride or potassium borohydride, or a combination of at least two thereof.
[0059] Preferably, the activation solution further comprises an acidic substance, and the acidic substance preferably comprises hydrochloric acid.
[0060] Preferably, the activation temperature is 20-70°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C or 65°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0061] Preferably, the activation time is 5-40 min, for example, it can be 10 min, 15 min, 20 min, 25 min, 30 min or 35 min, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0062] Preferably, the activation method comprises: mixing the sensitized polymer-coated microspheres with an acidic substance, adding a palladium salt (such as palladium chloride) solution to activate the microsphere surface to capture palladium ions, and then mixing it with a reducing agent to reduce the palladium ions to complete the activation.
[0063] Preferably, the method of depositing the metal layer is chemical deposition.
[0064] Preferably, the metal of the metal layer comprises any one of nickel, gold, copper, silver, tin or palladium, or a combination of at least two thereof, more preferably nickel and optionally gold.
[0065] Preferably, the chemical plating solution for depositing the metal layer comprises a mixture of a metal salt, a complexing agent, a reducing agent and a pH adjusting agent.
[0066] Preferably, the metal salt includes a nickel salt, and more preferably includes any one of nickel sulfate, nickel nitrate, nickel chloride or nickel acetate, or a combination of at least two thereof.
[0067] Preferably, the concentration of the metal salt in the chemical plating solution is 0.1-1 mol / L, for example, it can be 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L or 0.9 mol / L, etc.
[0068] Preferably, the complexing agent includes any one of sodium citrate, potassium citrate, potassium sodium tartrate, lactic acid or sodium lactate, or a combination of at least two thereof.
[0069] Preferably, the concentration of the complexing agent in the chemical plating solution is 0.01-1 mol / L, for example, it can be 0.02 mol / L, 0.05 mol / L, 0.08 mol / L, 0.1 mol / L, 0.12 mol / L, 0.15 mol / L, 0.18 mol / L, 0.0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, 0.6 mol / L, 0.7 mol / L, 0.8 mol / L or 0.9 mol / L, etc.
[0070] Preferably, the reducing agent comprises any one of hypophosphite, borohydride, dimethylamine borate or hydrazine, or a combination of at least two thereof.
[0071] Preferably, the reducing agent includes any one of sodium hypophosphite, potassium hypophosphite, sodium borohydride, potassium borohydride, dimethylamine borate or hydrazine, or a combination of at least two thereof.
[0072] Preferably, the pH adjuster is an acidic substance or an alkaline substance.
[0073] Preferably, the pH adjuster comprises an alkaline compound, more preferably sodium hydroxide.
[0074] Preferably, the deposition method comprises: dispersing the activated polymer-coated microspheres in a solvent to form a dispersion; introducing a first plating solution and a second plating solution into the dispersion at the same time under stirring conditions for deposition until no bubbles are generated in the system to obtain a metal layer; the first plating solution comprises a mixture of a metal salt and a complexing agent, and the second plating solution comprises a mixture of a reducing agent and a pH regulator.
[0075] Preferably, the solvent in the dispersion comprises a mixture of water, a complexing agent and a pH adjuster.
[0076] Preferably, the deposition temperature is 20-45°C, for example, it may be 22°C, 25°C, 28°C, 30°C, 32°C, 35°C, 38°C, 40°C, 42°C or 44°C, as well as specific point values between the above point values. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0077] Preferably, the chemically deposited metal layer comprises first depositing a nickel layer and then depositing a gold layer; the method for depositing the nickel layer is the aforementioned deposition method,
[0078] Preferably, the plating solution for depositing the gold layer comprises a combination of potassium gold cyanide, sodium citrate and disodium ethylenediaminetetraacetate.
[0079] Preferably, the concentration of potassium cyanogen gold in the plating solution is 0.001-0.1 mol / L (for example, 0.002 mol / L, 0.005 mol / L, 0.008 mol / L, 0.01 mol / L, 0.02 mol / L, 0.05 mol / L or 0.08 mol / L, etc.), and the concentration of sodium citrate is 0.01-1 mol / L (for example, 0.02 mol / L, 0.05 mol / L, 0.08 mol / L, 0.01 mol / L, 0.02 mol / L, 0.05 mol / L or 0.08 mol / L, etc.). .1mol / L, 0.2mol / L, 0.3mol / L, 0.5mol / L, 0.7mol / L or 0.9mol / L, etc.), and the concentration of disodium ethylenediaminetetraacetate is 0.01-1mol / L (for example, 0.02mol / L, 0.05mol / L, 0.08mol / L, 0.1mol / L, 0.2mol / L, 0.3mol / L, 0.5mol / L, 0.7mol / L or 0.9mol / L, etc.).
[0080] Preferably, the temperature of the deposited gold layer is 50-70°C, for example, 51°C, 53°C, 55°C, 57°C, 59°C, 60°C, 61°C, 63°C, 65°C, 67°C or 69°C, etc.
[0081] Preferably, the time for depositing the gold layer is 0.5-5 h, for example, 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h or 4.5 h.
[0082] Preferably, the preparation method comprises the following steps:
[0083] (1) subjecting the inner core microspheres to polymerization reaction with monomers in the presence of an initiator, an ionic surfactant and a solvent to obtain polymer-coated microspheres having a surface protrusion structure; the initiator is an oxidation-reduction initiation system, the solvent comprises a mixture of water and an organic solvent, and the mass ratio of water to organic solvent in the solvent is (1-20):1;
[0084] (2) The polymer-coated microspheres obtained in step (1) are sequentially subjected to functionalization, sensitization, activation and chemical deposition of a metal layer to obtain the conductive microspheres.
[0085] In a second aspect, the present invention provides a conductive microsphere having a surface protrusion structure, wherein the conductive microsphere is prepared by the preparation method described in the first aspect.
[0086] The conductive microspheres include an inner core microsphere, a polymer coating layer and a metal layer arranged in sequence from the inside to the outside; the polymer coating layer completely covers the inner core microsphere and has a surface protrusion structure, and the metal layer has a protrusion structure using the protrusion structure on the polymer coating layer as a template.
[0087] In a third aspect, the present invention provides an anisotropic conductive material, wherein the anisotropic conductive material comprises the conductive microspheres having a surface protrusion structure as described in the second aspect.
[0088] Preferably, the anisotropic conductive material includes anisotropic conductive tape, anisotropic conductive paste or anisotropic conductive sheet.
[0089] Preferably, the anisotropic conductive material comprises a combination of the conductive microspheres having the surface protrusion structure and a binder.
[0090] Compared with the prior art, the present invention has the following beneficial effects:
[0091] (1) The present invention, through the design of the preparation method, first polymerizes on the surface of the core microsphere to form a polymer coating layer having a protrusion structure with uniform distribution, controllable density and size, and then deposits metal on the polymer-coated microsphere to obtain a conductive microsphere with a surface protrusion structure. The protrusion structure on the conductive microsphere obtained by the preparation method has the characteristics of uniform distribution, high density, and controllable density and size. The core microsphere, protrusion structure and surface metal layer in the conductive microsphere are a closely connected integral structure with good structural integrity, strong pressure resistance and excellent stability, which effectively avoids the situation where the protrusion structure is damaged or the hard protrusion damages the electrode.
[0092] (2) The conductive microspheres with surface protrusion structures obtained by the preparation method have excellent and uniform conductive properties. The conductive microspheres have low resistance and good stability, and can maintain structural integrity under a pressure of 2 MPa. After being made into a conductive tape, the measured resistance is ≤2.4Ω, and can be as low as 1.7-2.4Ω, which significantly reduces the connection resistance, has high conductivity reliability and good stability, and is suitable for high-performance microelectrode connection. BRIEF DESCRIPTION OF THE DRAWINGS
[0093] Figure 1 This is a schematic diagram of the structure of the conductive microsphere with a surface protrusion structure in a specific embodiment; wherein 10 is a core microsphere, 20 is a polymer coating layer, and 30 is a metal layer;
[0094] Figure 2A This is a SEM image of the polymer-coated microspheres with surface protrusions obtained in step (1) of Example 1;
[0095] Figure 2B The SEM image of the conductive microspheres with surface protrusion structures provided in Example 1;
[0096] Figure 3A This is a SEM image of the polymer-coated microspheres with surface protrusions obtained in step (1) of Example 2;
[0097] Figure 3B The SEM image of the conductive microspheres with surface protrusions provided in Example 2;
[0098] Figure 4A This is a SEM image of the polymer-coated microspheres with surface protrusions obtained in step (1) of Example 3;
[0099] Figure 4B The SEM image of the conductive microspheres with surface protrusion structures provided in Example 3;
[0100] Figure 5A is a SEM image of the polymer-coated microspheres obtained in step (1) of Comparative Example 1;
[0101] Figure 5B The SEM image of the conductive microspheres provided for Comparative Example 1;
[0102] Fig. 6A is a SEM image of the polymer-coated microspheres obtained in step (1) of Comparative Example 2;
[0103] Figure 6B The SEM image of the conductive microspheres provided for Comparative Example 2;
[0104] Figure 7The SEM image of the conductive microspheres provided for Comparative Example 3;
[0105] Figure 8 This is a diagram showing the device effect for resistance testing;
[0106] Fig. 9 This is an optical picture of the conductive microspheres provided in Comparative Example 3 after completing the resistance test. DETAILED DESCRIPTION
[0107] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0108] As used herein, the terms "comprises," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a property, component, number, composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements but may also include other elements not expressly listed or elements inherent to such property, component, number, composition, step, method, article, or apparatus.
[0109] "Optionally", "optionally" or "either" means that the subsequently described matter or event can or cannot occur, and that the description includes instances where the event occurs and instances where it does not.
[0110] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.
[0111] In the present invention, the features defined as "first" or "second" may include one or more of the features explicitly or implicitly, and are used to distinguish and describe the features, without distinction of order or importance. In the description of the present invention, unless otherwise specified, "plurality" means two or more.
[0112] In the following specific embodiments of the present invention, the core microspheres, monomers, initiators, surfactants, solvents, etc. used are all commercially available chemicals and can be purchased through market channels.
[0113] In the following specific embodiments of the present invention, the morphology of the polymer-coated microspheres and the conductive microspheres is measured by scanning electron microscopy (SEM, FEI Q400 or Q250).
[0114] Example 1
[0115] A conductive microsphere with a surface protrusion structure and a preparation method thereof, the structural schematic diagram of the conductive microsphere with a surface protrusion structure is as follows Figure 1 As shown, it includes an inner core microsphere 10, a polymer coating layer 20 and a metal layer 30 arranged in sequence from the inside to the outside; the polymer coating layer 20 completely covers the inner core microsphere 10 and has a surface protrusion structure, and the metal layer 30 has a protrusion structure using the protrusion structure on the polymer coating layer 20 as a template.
[0116] The method for preparing the conductive microspheres having a surface protrusion structure comprises the following steps:
[0117] (1) Preparation of polymer-coated microspheres with surface protrusion structures:
[0118] 400.0 g of a core microsphere suspension with a core microsphere mass percentage of 12.5% (the core microspheres are polyacrylate microspheres with a particle size of 10 μm, and the solvent in the suspension is water), 150 g of deionized water and 50 g of anhydrous ethanol were added to a 2000 mL four-necked round-bottom flask, nitrogen was introduced, and the mixture was stirred and heated to 70°C.
[0119] Take 0.08g of sodium formaldehyde sulfoxylate and 3.6g of 10% sodium dodecylbenzene sulfonate aqueous solution, add 25.6g of deionized water to make a uniform aqueous solution for use;
[0120] Take 0.11g of tert-butyl hydroperoxide and mix it with 12.9g of deionized water to make a uniform aqueous solution for later use;
[0121] Take 2.8 g of methyl methacrylate and 11.5 g of glycidyl methacrylate and mix them to prepare a uniform monomer mixture;
[0122] Add 1.0 g of each of the two aqueous solutions mentioned above to the four-necked round-bottom flask every 15 minutes, and at the same time add 1.3 g of the monomer solution mentioned above to the four-necked round-bottom flask every 15 minutes; after the aqueous solution and the monomer mixture are added, continue stirring for 60 minutes, cool the flask to 25°C, filter and separate, and obtain the polymer-coated microspheres with surface protrusions.
[0123] (2) Functionalization:
[0124] Take 50.0g of the polymer-coated microspheres with surface protrusions obtained in step (1) and 200mL of anhydrous ethanol, add them to a 500mL round-bottom flask, stir and disperse them with magnetic stirring, add 50mL of ethylenediamine to the round-bottom flask, heat to 80°C and keep for 12h, then cool the flask to 25°C, filter and separate, and obtain functionalized polymer-coated microspheres.
[0125] (3) Sensitization and activation:
[0126] 1 g of the functionalized polymer-coated microspheres obtained in step (2) was added to 20 mL of an aqueous solution and ultrasonically dispersed for 30 min; 20 mL of a 20 g / L stannous chloride aqueous solution was added thereto, heated to 40°C, and stirred for 10 min to allow the tin ions to be adsorbed onto the surface of the microspheres to complete the sensitization treatment; the microspheres were filtered and washed with a 0.01 mol / L hydrochloric acid aqueous solution, and then dispersed with 20 mL of a 0.01 mol / L hydrochloric acid aqueous solution, and 20 mL of a 1.5 g / L palladium chloride solution was added, heated to 60°C, and stirred for 10 min to activate the microsphere surface to capture palladium ions; after filtering and washing with deionized water, the microspheres were dispersed in 20 mL of an aqueous solution, and 10 mL of a 10 g / L sodium hypophosphite aqueous solution was added under ultrasonic stirring conditions and maintained for 10 min to reduce the remaining palladium ions to obtain activated polymer-coated microspheres.
[0127] (4) Deposition of nickel layer:
[0128] The activated polymer-coated microspheres obtained in step (3) are added to 100 mL of a 0.1 mol / L sodium citrate aqueous solution. After ultrasonication for 30 min, the pH value is adjusted to 9 with 0.1 mol / L sodium hydroxide. The temperature is raised to 40° C. with stirring at a speed of 150 rpm. The first plating solution (containing an aqueous solution of 0.57 mol / L nickel sulfate and 0.1 mol / L sodium citrate) and the second plating solution (containing an aqueous solution of 1.40 mol / L sodium hypophosphite and 2 mol / L sodium hydroxide) are introduced into the solution at a speed of 1 mL / min. After all the two plating solutions are added, the temperature is maintained at 40° C. and stirring is continued until no bubbles are generated. The nickel layer is deposited to obtain the conductive microspheres having a surface protrusion structure.
[0129] The morphology of the product in this example was tested using a scanning electron microscope (SEM). Figure 2A The SEM image of the polymer-coated microspheres with surface protrusion structures obtained in step (1) has protrusion structures evenly distributed on the surface; Figure 2B The SEM image of the conductive microsphere with surface protrusion structure provided in this embodiment shows that the protrusion structure is evenly distributed on the surface.
[0130] Example 2
[0131] A conductive microsphere with a surface protrusion structure and a preparation method thereof, the preparation method comprising the following steps:
[0132] (1) Preparation of polymer-coated microspheres with surface protrusion structures:
[0133] 400.0 g of a core microsphere suspension with a core microsphere mass percentage of 12.5% (the core microspheres are polystyrene microspheres with a particle size of 10 μm, and the solvent in the suspension is water), 50 g of deionized water and 150 g of anhydrous ethanol were added to a 2000 mL four-necked round-bottom flask, nitrogen was introduced, and the mixture was stirred and heated to 70°C.
[0134] Take 0.08g of sodium formaldehyde sulfoxylate and 3.6g of 10% sodium dodecylbenzene sulfonate aqueous solution, add 25.6g of deionized water to make a uniform aqueous solution for use;
[0135] Take 0.11g of tert-butyl hydroperoxide and mix it with 12.9g of deionized water to make a uniform aqueous solution for later use;
[0136] Take 8g of styrene and 6.5g of glycidyl methacrylate and mix them to prepare a uniform monomer mixture;
[0137] Add 1.0 g of each of the two aqueous solutions mentioned above to the four-necked round-bottom flask every 15 minutes, and at the same time add 1.3 g of the monomer mixture mentioned above to the four-necked round-bottom flask every 15 minutes; after the aqueous solution and the monomer mixture are added, continue stirring for 60 minutes, cool the flask to 25°C, filter and separate, and obtain the polymer-coated microspheres with surface protrusions.
[0138] Steps (2) to (4) are carried out in the same manner as in Example 1 to obtain the conductive microspheres having a surface protrusion structure.
[0139] The morphology of the product in this example was tested using a scanning electron microscope (SEM). Figure 3A is a SEM image of the polymer-coated microspheres with surface protrusions obtained in step (1), Figure 3B The SEM images of the conductive microspheres with surface protrusion structures provided in this embodiment show that both surfaces have evenly distributed protrusion structures.
[0140] Example 3
[0141] A conductive microsphere with a surface protrusion structure and a preparation method thereof, the preparation method comprising the following steps:
[0142] (1) Preparation of polymer-coated microspheres with surface protrusion structures:
[0143] 400.0 g of a core microsphere suspension with a core microsphere mass percentage of 12.5% (the core microspheres are silicone microspheres with a particle size of 10 μm, and the solvent in the suspension is water), 120 g of deionized water and 80 g of anhydrous ethanol were added to a 2000 mL four-necked round-bottom flask, nitrogen was introduced, and the mixture was stirred and heated to 70°C.
[0144] Take 0.08g of sodium formaldehyde sulfoxylate and 3.6g of 10% sodium dodecylbenzene sulfonate aqueous solution, add 25.6g of deionized water to make a uniform aqueous solution for use;
[0145] Take 0.11g of tert-butyl hydroperoxide and mix it with 12.9g of deionized water to make a uniform aqueous solution for later use;
[0146] Take 2.8 g of styrene and 11.5 g of glycidyl methacrylate and mix them to prepare a uniform monomer mixture;
[0147] Add 1.0 g of each of the two aqueous solutions mentioned above to the four-necked round-bottom flask every 15 minutes, and at the same time add 1.3 g of the monomer mixture mentioned above to the four-necked round-bottom flask every 15 minutes; after the aqueous solution and the monomer mixture are added, continue stirring for 60 minutes, cool the flask to 25°C, filter and separate, and obtain the polymer-coated microspheres with surface protrusions.
[0148] Steps (2) to (4) are carried out in the same manner as in Example 1 to obtain the conductive microspheres having a surface protrusion structure.
[0149] The morphology of the product in this example was tested using a scanning electron microscope (SEM), wherein: Figure 4A is a SEM image of the polymer-coated microspheres with surface protrusions obtained in step (1), Figure 4B The SEM images of the conductive microspheres with surface protrusion structures provided in this embodiment show that the surfaces of the microspheres have protrusion structures evenly distributed.
[0150] The metal layer of the conductive microspheres with surface protrusion structures provided in Examples 1-3 is a nickel layer; the surface of the nickel layer can be further gold-plated by a replacement method, and the specific method includes: adding the conductive microspheres whose metal layer is a nickel layer to an aqueous solution containing 0.01 mol / L potassium gold cyanide, 0.2 mol / L sodium citrate and 0.2 mol / L disodium ethylenediaminetetraacetic acid, reacting at 60°C for 3 hours, filtering and washing, and obtaining gold-plated conductive microspheres with surface protrusion structures.
[0151] Comparative Example 1
[0152] A conductive microsphere and a preparation method thereof, the preparation method comprising the following steps:
[0153] (1) Preparation of polymer-coated microspheres:
[0154] 400.0 g of a core microsphere suspension having a core microsphere mass percentage of 12.5% (the core microspheres are the same as in Example 1) and 200 g of deionized water were added to a 2000 mL four-necked round-bottom flask, nitrogen was introduced, and the mixture was stirred and heated to 70° C.
[0155] Take 0.08g of sodium formaldehyde sulfoxylate and 3.6g of 10% sodium dodecylbenzene sulfonate aqueous solution, add 25.6g of deionized water to make a uniform aqueous solution for use;
[0156] Take 0.11g of tert-butyl hydroperoxide and mix it with 12.9g of deionized water to make a uniform aqueous solution for later use;
[0157] Take 2.8 g of methyl methacrylate and 11.5 g of glycidyl methacrylate and mix them to prepare a uniform monomer mixture;
[0158] Every 15 minutes, 1.0 g of each of the two aqueous solutions was added to the four-necked round-bottom flask, and at the same time, 1.3 g of the monomer mixture was added to the four-necked round-bottom flask. After the aqueous solution and the monomer mixture were added, stirring was continued for 60 minutes, the flask was cooled to 25° C., and the polymer-coated microspheres were obtained.
[0159] The conductive microspheres are obtained by carrying out steps (2) to (4) in the same manner as in Example 1.
[0160] The morphology of the product in this comparative example was tested using a scanning electron microscope. Figure 5A is the SEM image of the polymer-coated microspheres obtained in step (1), Figure 5B The SEM image of the conductive microspheres provided in this comparative example is combined with Figure 5A and Figure 5B It can be seen that the surface of the microspheres is smooth and has no protrusions.
[0161] Comparative Example 2
[0162] A conductive microsphere and a preparation method thereof, the preparation method comprising the following steps:
[0163] (1) Preparation of polymer-coated microspheres:
[0164] 400.0 g of a core microsphere suspension having a core microsphere mass percentage of 12.5% (the core microspheres are the same as in Example 1), 150 g of deionized water and 50 g of anhydrous ethanol were added to a 2000 mL four-necked round-bottom flask, nitrogen was introduced, and the mixture was stirred and heated to 70° C.
[0165] Take 0.08g of sodium formaldehyde sulfoxylate and add 25.6g of deionized water to make a uniform aqueous solution for later use;
[0166] Take 0.11g of tert-butyl hydroperoxide and mix it with 12.9g of deionized water to make a uniform aqueous solution for later use;
[0167] Take 2.8 g of methyl methacrylate and 0.03 g of glycidyl methacrylate, 11.5 g, and mix to form a uniform monomer mixture;
[0168] Every 15 minutes, 1.0 g of each of the two aqueous solutions was added to the four-necked round-bottom flask, and at the same time, 1.3 g of the monomer mixture was added to the four-necked round-bottom flask. After the aqueous solution and the monomer mixture were added, stirring was continued for 60 minutes, the flask was cooled to 25° C., and the polymer-coated microspheres were obtained.
[0169] The conductive microspheres are obtained by carrying out steps (2) to (4) in the same manner as in Example 1.
[0170] The morphology of the product in this comparative example was tested using a scanning electron microscope, wherein: Fig. 6A is the SEM image of the polymer-coated microspheres obtained in step (1), Figure 6B The SEM image of the conductive microspheres provided in this comparative example is combined with Fig. 6A and Figure 6B It can be seen that the surface of the microspheres is smooth and has no protrusions.
[0171] Comparative Example 3
[0172] A conductive microsphere with a surface protrusion structure and a preparation method thereof, the preparation method comprising the following steps:
[0173] Prepare polymer-coated microspheres according to the method in steps (1) to (3) in Comparative Example 1, and functionalize, sensitize and activate the microspheres;
[0174] (4) A nickel layer having a protrusion structure is prepared by using a method of producing protrusions by abnormal precipitation in a chemical nickel plating reaction:
[0175] The activated polymer-coated microspheres obtained in step (3) are added to 100 mL of a 0.1 mol / L sodium citrate aqueous solution, and after ultrasonication for 30 min, the pH value is adjusted to 9 with 0.1 mol / L sodium hydroxide, and the temperature is raised to 40° C. under stirring at a stirring speed of 150 rpm. 0.05 g of sodium docusate, a sanding agent for forming protrusions, is added, and a first plating solution (containing an aqueous solution of 0.57 mol / L nickel sulfate and 0.1 mol / L sodium citrate) and a second plating solution (containing an aqueous solution of 1.40 mol / L sodium hypophosphite and 2 mol / L sodium hydroxide) are simultaneously introduced therein at a speed of 1 mL / min, respectively. After all the two plating solutions are added, the temperature is maintained at 40° C. and stirring is continued until no bubbles are generated, thereby completing the deposition of the nickel layer and obtaining conductive microspheres with a surface protrusion structure.
[0176] The morphology of the conductive microspheres provided in this comparative example was tested using a scanning electron microscope (SEM). Figure 7 As shown, the surface has protrusion structures, but the distribution uniformity of the protrusion structures is poor.
[0177] The performance of the conductive microspheres provided in Examples 1-3 and Comparative Examples 1-3 was tested, and the specific method is as follows:
[0178] The conductive microspheres to be tested (the metal layer is a nickel layer) are made into anisotropic conductive tapes by an ACF tape manufacturer, connected to the ITO glass and the plastic circuit, and pressed at 2 MPa, 150°C, and 30 seconds to form a device for resistance testing. The effect is shown in the figure below. Figure 8 As shown. The resistance is tested by the Uni-T UT620B DC low resistance tester. This resistance includes the line resistance in the circuit, the resistance of the conductive microsphere itself, and the contact resistance between the microsphere and the circuit. Because the line resistance is fixed, the lower the measured resistance, the better the connection effect of the conductive microsphere; Figure 8 In the device shown, 18 sets of data of different circuits in the same device are tested according to the above method, and the range values of the 18 sets of data are shown in Table 1:
[0179] Table 1
[0180]
[0181]
[0182] According to the test data in Table 1, the present invention obtains conductive microspheres with surface protrusion structures by designing the preparation method. Figure 2B-Figure 4B It can be seen from the SEM image that the distribution of the surface protrusion structure is uniform and controllable, so that the conductive microspheres have excellent uniform conductive properties, and their resistance is 1.7-2.4Ω. Compared with the comparative examples 1-2 with smooth surfaces and no protrusion structures, the connection resistance is significantly reduced, which is suitable for high-performance microelectrode connections.
[0183] The conductive microspheres in Comparative Example 3 also have a protrusion structure, but the protrusion structure is prepared by abnormal precipitation in the chemical nickel plating reaction, the uniformity of the protrusion is poor, and the structural integrity and stability of the conductive microspheres are not good. When preparing the test device, they are damaged under a pressure of 2 MPa, resulting in a high measured resistance value and poor conductivity. Fig. 9 The optical picture of the conductive microspheres provided for comparative example 3 after completing the resistance test shows that the conductive microspheres are obviously damaged.
[0184] The applicant declares that the present invention uses the above-mentioned embodiments to illustrate the conductive microspheres with surface protrusion structures and the preparation method and application thereof, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a conductive microsphere having a surface protrusion structure, characterized in that: The preparation method comprises: The inner core microspheres and the monomers are polymerized in the presence of an initiator, a surfactant and a solvent to obtain polymer-coated microspheres with surface protrusions; the solvent comprises a mixture of water and an organic solvent; The mass ratio of water to organic solvent in the solvent is (1-20):1; The polymer-coated microspheres are sequentially functionalized, activated and metal layer deposited to obtain the conductive microspheres; The monomers include (meth)acrylate monomers and / or alkenyl aromatic monomers; The surfactant is an anionic surfactant; The HLB value of the surfactant is ≥10; The organic solvent includes an alcohol solvent.
2. The preparation method according to claim 1, characterized in that: The core microspheres include inorganic microspheres and / or polymer microspheres.
3. The preparation method according to claim 2, characterized in that: The inner core microspheres include any one of polystyrene microspheres, polyacrylate microspheres, styrene-acrylate copolymer microspheres, organic silicon microspheres, silicon dioxide microspheres or zirconium oxide microspheres, or a combination of at least two thereof.
4. The preparation method according to claim 1, characterized in that: The mass ratio of the monomer to the core microsphere is (0.01-1):
1.
5. The preparation method according to claim 1, characterized in that: The initiator includes an oxidation-reduction initiation system.
6. The preparation method according to claim 5, characterized in that: The oxidant in the oxidation-reduction initiation system includes any one of persulfate, hydrogen peroxide or organic peroxide, or a combination of at least two of them.
7. The preparation method according to claim 5, characterized in that: The reducing agent in the oxidation-reduction initiation system includes any one of sodium formaldehyde sulfoxylate, sodium sulfite, sodium bisulfite, ferrous salts, cyclopentane salts, sodium dithionite, tertiary amine compounds or mercaptans, or a combination of at least two thereof.
8. The preparation method according to claim 1, characterized in that: The polymerization temperature is 50-90°C.
9. The preparation method according to claim 1, characterized in that: The polymerization reaction time is 0.5-6 h.
10. The preparation method according to claim 1, characterized in that: The functionalization method is to make the polymer-coated microspheres contain functional groups, and the functional groups include any one of hydroxyl, carboxyl, amino, thiol or triphenylphosphine, or a combination of at least two of them.
11. The preparation method according to claim 1, characterized in that: The functionalized reagent includes any one of a hydroxyl-containing compound, a carboxyl-containing compound or an amino-containing compound, or a combination of at least two of them.
12. The preparation method according to claim 11, characterized in that: The mass ratio of the functionalized reagent to the polymer-coated microspheres is (0.1-2):
1.
13. The preparation method according to claim 1, characterized in that: The functionalization temperature is 50-100°C.
14. The preparation method according to claim 1, characterized in that: The functionalization time is 5-24 h.
15. The preparation method according to claim 1, characterized in that: A sensitization step is also included between the functionalization and activation.
16. The preparation method according to claim 15, characterized in that: The sensitizing solution is stannous chloride solution.
17. The preparation method according to claim 15, characterized in that: The sensitization temperature is 30-50°C.
18. The preparation method according to claim 15, characterized in that: The sensitization time is 1-30 min.
19. The preparation method according to claim 1, characterized in that: The activated solution comprises a mixture of a palladium salt and a reducing agent.
20. The preparation method according to claim 19, characterized in that: The reducing agent includes any one of hypophosphite, phosphite or borohydride or a combination of at least two thereof.
21. The preparation method according to claim 19, characterized in that: The activation solution also includes an acidic substance.
22. The preparation method according to claim 1, characterized in that: The activation temperature is 20-70°C.
23. The preparation method according to claim 1, characterized in that: The activation time is 5-40 min.
24. The preparation method according to claim 1, characterized in that: The method for depositing the metal layer is chemical deposition.
25. The preparation method according to claim 1, characterized in that: The metal of the metal layer includes any one of nickel, gold, copper, silver, tin or palladium, or a combination of at least two thereof.
26. The preparation method according to claim 1, characterized in that: The chemical plating solution for depositing the metal layer includes a mixture of a metal salt, a complexing agent, a reducing agent and a pH adjusting agent.
27. The preparation method according to claim 26, characterized in that: The complexing agent includes any one of sodium citrate, potassium citrate, potassium sodium tartrate, lactic acid or sodium lactate, or a combination of at least two thereof.
28. The preparation method according to claim 26, characterized in that: The reducing agent includes any one of hypophosphite, borohydride, dimethylamine borate or hydrazine, or a combination of at least two thereof.
29. The preparation method according to claim 26, characterized in that: The pH adjuster includes a basic compound.
30. The preparation method according to claim 1, characterized in that: The deposition temperature is 20-45°C.
31. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) subjecting the core microspheres to polymerization reaction with monomers in the presence of an initiator, an ionic surfactant and a solvent to obtain polymer-coated microspheres having a surface protrusion structure; the initiator is an oxidation-reduction initiation system, the solvent comprises a mixture of water and an organic solvent, and the mass ratio of water to organic solvent in the solvent is (1-20):1; (2) The polymer-coated microspheres obtained in step (1) are sequentially subjected to functionalization, sensitization, activation and chemical deposition of a metal layer to obtain the conductive microspheres.
32. A conductive microsphere having a surface protrusion structure, characterized in that: The conductive microspheres are prepared by the preparation method according to any one of claims 1 to 31.
33. An anisotropic conductive material, characterized in that: The anisotropic conductive material includes the conductive microspheres having a surface protrusion structure as described in claim 32.
Citation Information
Patent Citations
Conductive fine particles and anisotropic conductive material
CN101006525A
Conductive powder, conductive material containing the conductive powder, and method for manufacturing the conductive powder
CN103222013A
Conductive particles, conductive material and connection structure
CN103748637A
Preparation method of conductive material-made composite microsphere
CN102977395A